Uptake of dissolved inorganic nitrogen and N2 fixation by Crocosphaera watsonii under climate change scenarios - Umbricht, Jacqueline; Filella, Alba; Klett, Angelina; Vogts, Angela; Benavides, Mar; Voss, Maren (Frontiers in Marine Science, 2024)
The response of N2 fixation to projected future conditions in the ocean cannot be reliably predicted to date. We conducted a minicosm experiment with pre-acclimated cultures of the globally significant diazotroph Crocosphaera watsonii strain WH8501 (“Crocosphaera”). PH and temperature were altered simultaneously to match the RCP scenarios 4.5 and 6 and investigate a more realistic future scenario compared to studies that focus on changes of a single stressor only. The cell abundance and nitrogen metabolism of Crocosphaera was monitored over 5 days. Our results imply that Crocosphaera is able to simultaneously perform N2 fixation and assimilate dissolved inorganic nitrogen (DIN, i.e., nitrate and ammonium) under all the conditions tested and implies a competition with non-diazotrophic phytoplankton for DIN, which should be further investigated. Using NanoSIMS analysis of single cells, our results point towards a preference for DIN assimilation over N2 fixation under more acidic and warmer conditions. Overall, our results show that while the combined alteration of pH and temperature had a negative effect on the diazotroph’s growth and N2 fixation, Crocosphaera is likely to cope well with conditions in the future ocean. The high intra-population variability in nitrogen assimilation pathways may give this species the flexibility to quickly react to environmental changes.